2016
DOI: 10.1007/s11356-016-7301-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute, chronic and biochemical effects of chlorothalonil on Agalychnis callidryas, Isthmohyla pseudopuma and Smilisca baudinii tadpoles

Abstract: Declines of amphibian populations have been a worldwide issue of concern for the scientific community during the last several decades. Efforts are being carried out to elucidate factors related to this phenomenon. Among these factors, pathogens, climate change, and environmental pollution have been suggested as possible causes. Regarding environmental pollutants, some pesticides are persistent in the environment and capable of being transported long distances from their release point. In Costa Rica, some pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The tadpole developmental stage may be more relevant to determining toxicity than tadpole age. In a study carried out in Costa Rica, it was found that chlorothalonil (fungicide) is highly toxic to native amphibian species and that low concentrations can cause biochemical responses related to phase II of biotransformation and effects on development [19].…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tadpole developmental stage may be more relevant to determining toxicity than tadpole age. In a study carried out in Costa Rica, it was found that chlorothalonil (fungicide) is highly toxic to native amphibian species and that low concentrations can cause biochemical responses related to phase II of biotransformation and effects on development [19].…”
Section: -Discussionmentioning
confidence: 99%
“…Existing risk assessment procedures for pesticide regulation are not protecting amphibians [18]. Declines of amphibian populations have been a worldwide issue of concern for the scientific community during the last several decades [19]. Indeed, amphibians may be at greater risk of toxic effects of pesticides than other aquatic vertebrates because their preferred breeding habitats are often shallow lentic or ephemeral water bodies [3].…”
Section: -Introductionmentioning
confidence: 99%
“…Chlorothalonil (chloronitrile) is a low‐cost, broad‐spectrum, nonsystemic fungicide that also has antibacterial, anti‐algal and insecticidal properties. While it is widely used in the field, it has been listed by EPA as a likely carcinogen (EPA‐738‐F‐99‐008, April 1999) possibly with major negative effects on the environment (Méndez et al ., ). Chlorothalonil effects are mediated by reducing fungal intracellular glutathione molecules, making this important cellular antioxidant ineffective, while at the same time preventing essential enzymatic reactions that use specific conformations of glutathione as their reaction centres (Tillman et al ., ; Yang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…As alluded to above, if used properly during early flowering (Yoshida et al ., ) they can reduce FHB spread. However, increases in fungicide resistance and environmental problems caused by these conventional fungicides is an increasing concern (Brown et al ., ; Méndez et al ., ; Yan et al ., ; Zhou et al ., ). Chlorothalonil (chloronitrile) is a low‐cost, broad‐spectrum, nonsystemic fungicide that also has antibacterial, anti‐algal and insecticidal properties.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies, however, have been conducted to understand the fate and effects of pesticides for the (sub-) tropical freshwater environments over the last decades. These study included single species toxcitity tests (Maltby et al, 2005;Kwok et al, 2007;Freitas and Rocha, 2012;Mansano et al, 2016;Daam and Rico, 2016;Amid et al, 2017), multiple species toxicity tests (Rico et al, 2010(Rico et al, , 2011Echeverría-Sáenz et al, 2016;Méndez et al, 2016;Stadlinger et al, 2016;Svensson et al, 2017) and model ecosytem studies (i.e. microcosms) (Laabs et al, 2007;Daam et al, 2008aDaam et al, , 2008bDaam et al, , 2009aDaam et al, , 2009bDaam et al, , 2010Van den Brink, 2010, 2011;Leboulanger et al, 2011).…”
Section: Effects Of Pesticides On (Sub-) Tropical Aquatic Ecosystemsmentioning
confidence: 99%